Use of aldol condensation between furfural and acetone for biofuel production: A review - Tayla Luiza Pereira Borges; Rejane de Castro Santana; André Gustavo Sato; Fábio de Ávila Rodrigues (The Journal of Engineering and Exact Sciences)
The continued reliance on fossil fuels and the associated environmental challenges have spurred the development of renewable energy sources, with biorefineries emerging as a prominent solution for converting biomass into valuable fuels and platform chemicals. Among these, the production of furfural, derived from C5 sugars in lignocellulosic materials, holds particular significance. Extended-chain hydrocarbon fuels and intermediates, such as 4-(2-furyl)-3-buten-2-one (FAc, C8) and 1,4-pentadiene-3-one-1,5-di-2-furanyl (F2Ac, C13), are synthesized via aldol condensation between furfural and acetone, followed by hydrogenation and hydrodeoxygenation processes. This study emphasizes the critical role of catalysts, particularly heterogeneous catalysts, in increasing the efficiency and selectivity of these reactions. Solid catalysts, compared to their homogeneous counterparts, offer substantial advantages, including ease of recovery, reusability, and increased sustainability. Advances in analytical techniques, such as gas chromatography-mass spectrometry (GC-MS) and other state-of-the-art methods, have been instrumental in refining the characterization of heterogeneous catalysts, ensuring improved product quality and process optimization. Additionally, the study explores cutting-edge methodologies for catalyst characterization, utilizing tools such as field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), and inductively coupled plasma optical emission spectroscopy (ICP-OES) to obtain precise quantitative and qualitative insights. This review provides a detailed analysis of the integration of these technologies into biofuel production, highlighting the critical role of innovative catalysts—particularly bifunctional systems under controlled conditions—and the development of optimized conversion routes. These strategies are essential for advancing industrial efficiency, improving process selectivity, and contributing to the sustainability of the energy sector.